The limits of anticolonialism: the British Labour movement and the end of the empire in Guiana - Mawby, Spencer (Wiley, 2016)
The Labour Party’s ambivalent attitude to anticolonial nationalism is well known but its place in the conflicts between the party’s revisionists and the left has been less fully elaborated, while the influence of British trade unions in the formation of party policy on decolonisation has been cast to the margins of the historiography. Events in British Guiana are representative of this trend because, while the activities of the American Federation of Labor-Congress of Industrial Organizations have been detailed by a number of historians, including Stephen Rabe, Robert Waters, Gary Daniels and Lily Ramcharan, the impact of the British TUC has been largely ignored. A study of the international labour politics of the 1950s and 1960s suggests both that the fate of the Guianese left was inextricably tied to conflicts in the British Labour party and that trade union leaders in the metropolis offered powerful support to revisionists in making the case for prioritising Atlanticism over colonial liberation. The Labour Party’s support for the suspension of the Guianese constitution by the Churchill government in 1953 and their willingness to implement Conservative plans for constitutional reform in 1964 demonstrate that the party’s liberationist faction were unable to overturn the Cold War agenda espoused by the right wing of the parliamentary party and anti-communists in the trade union movement.